A Novel Continuously Recording Approach for Unraveling Ontogenetic Development of Sleep-Wake Cycle in Rats - Cui, Guang-Fu; Hou, Min; Shao, Yu-Feng; Chen, Hai-Lin; Gao, Jin-Xian; Xie, Jun-Fan; Chen, Yu-Nong; Cong, Chao-Yu; Dai, Feng-Qiu; Hou, Yi-Ping (Frontiers in Neurology, 2019)
Sleep-wake development in postnatal rodent life could reflect the brain maturational stages. As the altricial rodents, rats are born in a very undeveloped state. Continuous sleep recording is necessary to study the sleep-wake cycle profiles. However, it is difficult to realize in infant rats since they rely on periodic feeding before weaning and constant warming and appropriate EEG electrodes. We developed a new approach including two types of EEG electrodes and milk-feeding system and temperature-controlled incubator to make continuously polysomnographic (PSG) recording possible. The results showed that there was no evident difference in weight gaining and behaviors between pups fed through the milk-feeding system and warmed with temperature-controlled incubator and those kept with their dam. Evolutional profiles of EEG and electromyogram (EMG) activities across sleep-wake states were achieved perfectly during dark and light period from postnatal day (P) 11 to P75 rats. The ontogenetic features of sleep-wake states displayed that the proportion of rapid eye movement (REM) was 57.0 ± 2.4% and 59.7 ± 1.7% and non-REM (NREM) sleep was 5.2 ± 0.8% and 4.9 ± 0.5% respectively, in dark and light phase at P11, and then REM sleep progressively decreased and NREM sleep increased with age. At P75, REM sleep in dark and light phase respectively, reduced to 6.3 ± 0.6% and 6.9 ± 0.5%, while NREM correspondingly increased to 37.5 ± 2.1% and 58.4 ± 1.7%. Wakefulness from P11 to P75 in dark phase increased from 37.8 ± 2.2% to 56.2 ± 2.6%, but the change in light phase was not obvious. P20 pups began to sleep more in light phase than in dark phase. The episode number of vigilance states progressively decreased with age, while the mean duration of that significantly increased. EEG power spectra in 0.5–4 Hz increased with age accompanied with prolonged duration of cortical slow wave activity. Results also indicated that the dramatic changes of sleep-wake cycle mainly occurred in the first month after birth. The novel approaches used in our study are reliable and valid for continuous PSG recording for infant rats and unravel the ontogenetic features of sleep-wake cycle.